Resonance Two-Photon Ionization of Diarylethene in the Presence of Cyclodextrin - Michihiro Hara; Makoto Miwa; Tatsuya Takeshita; Shouhei Watanabe (International Journal of Photoenergy)
The transient absorption of the diarylethene 1,2-bis(2,4-dimethyl-5-phenyl-3-thienyl)-3,3,4,4,5,5-hexafluoro-1-cyclopentene (DE) was measured using 266 nm laser flash photolysis in the presence of various cyclodextrins (CDs) in aqueous solvent. Ionization of DE occurred within the laser flash (5 ns) to give the DE radical cation and water-solvated electron. The electron was generated by two-photon excitation through simultaneous irradiation with 266 nm laser light, and the ionization quantum yields of DE in the presence of α-CD, β-CD, m-β-CD, and γ-CD depended on the properties of the DE/CD complexes. These results suggest that useful two-photon ionization occurred for these complexes. The ionization quantum yield of DE was found to increase in aqueous solution after the addition of m-β-CD (50 mM), in which m-β-CD likely controlled the photochromic reactivity of DE.